The effect of covid-19 on herding behavior: Evidence from African emerging markets - TAN, ÖMER FARUK (My University, 2023)
The emergence of Coronavirus Disease (COVID-19) pandemic, which spread all over the world, created a shock effect on financial markets as in all areas. With fear and panic, investors couldn’t make rational decisions and tried to imitate what other investors were doing. Unlike the idea of the efficient market hypothesis, investors showed herd behavior during the emergence of the pandemic. Hence, this paper investigates whether COVID-19 increased herding behavior in African emerging markets. We use a sample from the Johannesburg Stock Exchanges (JSE) and the Egyptian Exchange (EGX) for the period from January 4, 2010, to June 30, 2020. We find strong evidence of the presence of herding behavior in both stock markets during the COVID-19 period. Robust results are found in different sub-periods. The result of the study is important to help individual and institutional investors as well as financial regulators to find a solution to prevent herd behavior.

Tüm dünyayı etkisi altına alan Koronavirüs Pandemisinin (COVID-19) ortaya çıkması ile finansal piyasalar üzerinde de şok etkisi yaratmıştır. Korku ve paniğe kapılan yatırımcılar rasyonel bir karar verememiştir ve diğer yatırımcıların almış oldukları kararları taklit etmeye çalışmışlardır. Etkin piyasalar hipotezinden farklı olarak yatırımcılar bu süreçte sürü davranışı göstermiştir. Bu nedenle, bu makale COVID-19’un gelişmekte olan Afrika pazarlarında sürü davranışını artırıp artırmadığını araştırmaktadır. Çalışmada Johannesburg ve Mısır Borsaları 04 Ocak 2010- 30 Haziran 2020 yılları arasında örneklem olarak kullanılmıştır. Analiz sonuçlarına göre COVID-19 döneminde güçlü bir sürü davranışı görüldüğü ortaya çıkmıştır. Farklı alt periyotlarda da bulduğumuz sonuç doğrulanmıştır. Çalışmanın sonucu, bireysel ve kurumsal yatırımcıların yanı sıra finansal piyasa düzenleyicilerin sürü davranışını önlemeye yönelik bir çözüm bulmasına yardımcı olması açısından önemlidir.
Covıd-19’un sürü davranışı üzerindeki etkisi: Gelişmekte olan Afrika ülkeleri örneği
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Finansal Piyasalar ve Yatırım Yönetimi; Social Sciences and Humanities; Management; Financial Markets and Investment Management; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; COVID-19; Herding Behavior; South Africa; Egypt; Emerging Markets; Sürü Davranışı; Güney Afrika; Mısır; Gelişmekte Olan Ülkeler